Galvanized : the odyssey of a reluctant Carolina Confederate - Brantley, Michael K. (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"The story of a North Carolina farmer who fought in the Civil War. Wright Stephen Batchelor served in both armies, survived Gettysburg, was twice captured and spent time in the worst POW camps of the war, escaped, and walked hundreds of miles to rejoin his comrades at Petersburg just in time for a Union siege. After surviving it all, he went home to North Carolina only to be the victim of a bizarre murder"--